2001
DOI: 10.1177/104063870101300403
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Direct Flow Cytometric Erythrocyte Immunofluorescence Assay in Dogs with Immune-Mediated Hemolytic Anemia and Comparison to the Direct Antiglobulin Test

Abstract: A direct flow cytometric erythrocyte immunofluorescence assay (FC) was developed and compared with the direct antiglobulin test (DAT) for detection of erythrocyte-bound immunoglobulin (IgG and IgM) and complement (C3) in dogs with immune-mediated hemolytic anemia (IMHA). Tests were performed on erythrocytes from 13 healthy nonanemic dogs and from 13 anemic dogs with IMHA. The FC and DAT were negative for erythrocyte-bound immunoglobulin in all healthy dogs. The FC was negative for erythrocyte-bound C3 in 12 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
21

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 15 publications
0
37
0
21
Order By: Relevance
“…In some dogs with IMHA, the target antigens for RBC autoantibodies have been identified, although in most dogs with IMHA the antigens are unknown 8 . Previous studies have found that both immunoglobulin (Ig) G and IgM antibodies can be detected on the surface of RBC 7,9–13 . The primary consequence of antibody binding to the RBC surface is premature removal of RBC from circulation by macrophages in the spleen and liver 2–4 …”
mentioning
confidence: 99%
“…In some dogs with IMHA, the target antigens for RBC autoantibodies have been identified, although in most dogs with IMHA the antigens are unknown 8 . Previous studies have found that both immunoglobulin (Ig) G and IgM antibodies can be detected on the surface of RBC 7,9–13 . The primary consequence of antibody binding to the RBC surface is premature removal of RBC from circulation by macrophages in the spleen and liver 2–4 …”
mentioning
confidence: 99%
“…A anemia hemolítica imuno-mediada (AHIM) é a causa mais comum dentre as anemias hemolíticas e a doença imuno-mediada de maior prevalência em cães (Mackin 2000, Quigley et al 2001, McCullough 2003, Giger 2005. A AHIM é caracterizada pela destruição direta ou fagocitose de hemácias opsonizadas por imunoglobulinas como IgG ou IgM e/ou complemento.…”
Section: Introductionunclassified
“…Immunofluorescence Assay: The presence of IgG and/or IgM antibodies on the plasma membrane of erythrocytes and platelets was examined by flow cytometry according to the method described by Quigley et al (2001) on whole blood collected from all rats/group on week 5 (erythrocyte) and from the first 5 rats/group from the control, middose females, and high-dose males on week 10 (platelets). Antibodies used were the goat anti-rat IgG FITC (Bethyl Laboratories, Montgomery, TX) and mouse anti-rat IgM FITC (Clone HIS49; BD Bioscience, San Jose, CA).…”
Section: Direct Flow Cytometric Erythrocyte and Plateletmentioning
confidence: 99%